Persistence of a high-risk opportunistic pathogen amid compartment-resolved antibiotic resistance attenuation in acute shock-loaded micro-wetlands - Rong-min Zhang; Zi-yao Liu; Hui-ting Chen; Xin-ce Yang; Liwei Shi; Yi-cheng Zhang; Xin-ting Li; Lin-lin Yang; Jing-yu Xu; Xin-lei Lian; Li Li; Xian-hui Huang; et al. (Journal of Environmental Chemical Engineering, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Scale up fermentation of Chenopodium formosanum dairy products with process optimization and evaluation of ACE inhibitory peptides and antioxidant activity - Chen-Che Hsieh; Jing-Rong Wu; Yi-Cheng Huang; Shin-Ping Lin; Jheng-Jhe Lu; Adyasa Barik; Shella Permatasari Santoso; Chang-Wei Hsieh; Hui-Wen Lin; Kuan-Chen Cheng (Food Bioscience, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A case study on indoor air quality assessments and health risk implications across diverse university environments - Jheng Fong Tsai; Yu-Hsiang Cheng; Zong-Rong Chen; Chi-Chi Lin (Atmospheric Pollution Research, 2026)

Drying-wetting cycles alter the balance between physical fragmentation and leaching during leaf litter decomposition: a laboratory incubation experiment - Le-Lin Yu; Rui-Jing Chai; Qi-Han Tu; An He; Le-Cheng Ai; Rong Mao (Plant and Soil, 2026)

Chemical constituents and ferroptosis inhibitory activity of the deep-sea-derived fungus Penicillium citrinum W24 - Cheng-You Lin; Yuan Wang; Tai-Zong Wu; Rong Chao; Zheng-Biao Zou; Li-Sheng Li; Tian-Hua Zhong; Xian-Wen Yang (Natural Product Research, 2026)

Sulfonylurea receptor integrates calcium homeostasis and insulin-like peptide signaling to regulate energy metabolism and larval development in Hyphantria cunea - Yue-Cheng Zhao; Rong-Man Gou; Haneef Tariq; Xi-Lin Li; Lian-Sheng Zang; Li-Wen Song (Insect Biochemistry and Molecular Biology, 2026)

Introducing Double-Moment Warm Rain Physics into the Goddard 4ICE Microphysics Scheme - Kao-Shen Chung; Yu-Jyun Liou; Cheng-Rong You; Zhao-Cheng Zeng; Pay-Liam Lin; Donghai Wang; Wei-Kuo Tao; Stephen Lang; Takamichi Iguchi; Adrian Loftus; Jiun-Dar Chern (Asia-Pacific Journal of Atmospheric Sciences, 2026)
In this study, a new double-moment warm rain Goddard 4ICE scheme (GCEDM) is developed based on the Goddard 4ICE single-moment (GCESM) scheme and then tested using idealized 2D squall line and 3D supercell simulations. The addition of the total number concentrations for cloud water ( $$\:N_{TC}$$ ) and rainwater ( $$\:N_{TR}$$ ) enables this new scheme to simulate more diverse raindrop size distributions, making it more realistic. GCEDM has similar overall thermal and dynamic characteristics to GCESM but produces higher evaporation rates, predicted particle number concentrations, and mass mixing ratios than GCESM, leading to stronger cold pools than with GCESM. In addition, comparisons are made versus the Weather Research and Forecasting Model Double-Moment Microphysics 7-class scheme (WDM7), which was also improved from a single-moment 4-class ice scheme to a double-moment warm-rain scheme. WDM7 also shows a stronger cold pool, but the system characteristics and microphysical processes are quite different from the single-moment version of this scheme.

Elucidating the role of overlooked environmentally persistent free radicals and reactive chlorine species on photoaged chlorine-containing microplastics: New insights into formation mechanisms and health risks - Linyang Xie; Jingbo Ling; Kaiyou Huang; Jianyu Lin; Hongjian Li; Zhiyu Zhou; Shixiang Gao; Rong Ji; Cheng Gu; Dongmei Zhou; Xueyuan Gu (Journal of Hazardous Materials, 2026)

Ti(IV)-incorporated covalent organic frameworks for efficient dark-photocatalytic reduction of U(VI) - Li-Ling Chen; Cheng-Peng Niu; Rui Zhang; Yun-Peng Wu; Zhen-Wen Zhang; Bin Lin; Cheng-Rong Zhang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2026)

A novel strategy for controlling nitrite accumulation in fermented cabbage by regulating microbial community structure via cold plasma - Lin Zhu; Mengke Cheng; Yuan Wang; Xinyu Hu; Rong Wang; Biyue Yang; Xiang Xiao; Wei Wei (Food Control, 2026)

Mechanoluminescent Janus architecture for stimulus-responsive photodynamic therapy - Rong-Kai Du; Xu-Lin He; Qing-Qing Jin; Hong Liang; Tai-Zhong Xiao; Lei Zhong; Jun-Cheng Zhang; Tian-Ying Sun; Lei Zhou; Ming-Mei Wu (Chemical Engineering Journal, 2026)

Microbial processing of organic matter in cold seep sediments revealed by amino compound distributions and degradation indices - Yang Wu; Lina Lyu; Meiqing Lin; Shengtao Ma; Cheng Yang; Rong Wu; Kaiqin Huang; Xi Xiao; Yifei Dong; Binbin Guo; Danyi Su; Jing Zhao; et al. (Marine Pollution Bulletin, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Characterization of neutral fluids in the volcanic geothermal system under the Tatun Volcano Group, Taiwan - Yi-Chia Lu; Chyi Wang; Sheng-Rong Song; Pei-Ling Wang; Ting-Jui Song; Sachihiro Taguchi; Tsung-Ren Peng; Li-Hung Lin; Jian-Cheng Lee; Hong-Chun Li (Journal of Geochemical Exploration, 2025)

Integrated assessment of wind energy's emission and meteorological effects on PM2.5 in Taiwan - I-Chun Tsai; Pei-Rong Hsieh; Cheng-Wei Lin; Chung-Cheh Chou; Chia-Ying Tu; Chao-Tzuen Cheng; Huang-Hsiung Hsu (Journal of Environmental Management, 2025)

Morphology and nutrient content of bamboo rhizomes: Responses to enclosure succession in a Phyllostachys edulis forest in Wuyi Mountains, China - Xing Cai; Rui Cheng; Zhenhua Chen; Jiannan Lin; Min Wu; Jiaying Liu; Jihong Xiao; Yuchen Lin; Lingyan Chen; Yirong Zhang; Jundong Rong; Tianyou He; et al. (Forest Ecology and Management, 2025)

Mechanical performance analysis of fully grouted bolts considering yield and hardening characteristics - Akang Li; Hua Cheng; Zhongwen Yue; Chuanxin Rong; Peng Wang; Jian Lin (International Journal of Rock Mechanics and Mining Sciences, 2025)

System temperature prediction and verification of all-sky electrostatic analyzer on the lunar surface - Tsung-Pin Hung; Chih-Yu Chiang; Tzu-Fang Chang; Zhao-Yu Huang; Yu-Rong Cheng; Sheng-Cheng Tsai; Tzu-En Yen; Jih-Run Tsai; Shin-Fa Lin (Advances in Space Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Cadmium exposure causes trophoblast abnormal syncytization and endocrine dysfunction in preeclampsia - Weilong Lin; Xuemeng Li; Xiangyou An; Jiancai Yin; Ziyan Zhao; Xiaorui Yan; Rong Xu; Baojing Zhao; Xue Du; Huiru Cheng; Zhen Yu; Yuanyuan Yang (Reproductive Toxicology, 2025)

Single and joint associations of exposure to polycyclic aromatic hydrocarbons with hypertensive disorders of pregnancy: A nested case-control study - Rui Yu; Cheng Chen; Mingyu Deng; Nian Wu; Yanling Xiao; Songlin An; Lin Tao; Xingting Zheng; Jing Yang; Zhongmei Hu; Pei Xu; Xingyan Liu; et al. (Environmental Pollution, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Insights into Leuconostoc-clade as starters in Chinese paocai: Shaping microbial communities for rapid, safe, and flavor-preserving fermentation - Xinyu Hu; Mengke Cheng; Meng Zhang; Biyue Yang; Rong Wang; Juan Bai; Jiayan Zhang; Wei Wei; Lin Zhu; Xiang Xiao (Food Bioscience, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Effect of culturing factors on the production of biomass and secondary metabolites in ginseng adventitious root cultures for new resource food - Hang-Lin Song; Zheng-Hai Cheng; Rong-De Jin; Chun-Guang Liu; Xiang-Hong Ma; Jun-Nan Wu; Xi-Hua Cui (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Synergistic properties of single-component hexagonal iron borate for superior and sustainable photo-Fenton catalysis - Po-Yi Wu; Jing-Cheng Hsu; Tsung-Yueh Lin; Yu-Lun Zhu; Yu-Rong Chang; Pei Yuin Keng (Journal of Environmental Chemical Engineering, 2025)

Terpenoids with Antiangiogenic Activity from Formosan Soft Coral Caementabunda hypotentaculata - Hsin Huang; Chen-Yu Yang; Shih-Wei Wang; Limbadri Salendra; Shu-Rong Chen; Tzi-Yi Ke; Yu-Liang Yang; Yu-Chi Lin; Yuan-Bin Cheng (Marine Biotechnology, 2025)

The influence of PM2.5 exposure on SARS-CoV-2 infection via modulating the expression of angiotensin converting enzyme II - Meng-Wei Lin; Cheng-Han Lin; Jia-Rong Chang; Hua-Hsin Chiang; Ting-Hsuan Wu; Chih-Sheng Lin (Journal of Hazardous Materials, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Highly active Cu-embedded in magnetic carbon nanofibers for the reduction of 4-nitrophenol - Ching-Shiun Chen; Tse-Ching Chen; Kai-Lin Chiu; Cheng-Rong Hsing; Li-Yu Wang; Chia-Min Yang; Chih-Wen Pao; Chi-Liang Chen (Chemical Engineering Journal, 2025)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

PM2.5 constituents associated with mortality and kidney failure in childhood-onset lupus nephritis: A 19-year cohort study - Guohua He; Yaqi Wang; Cheng Cheng; Jianhui Guo; Zhilang Lin; Ziyun Liang; Bei Jin; Liyuan Tao; Liping Rong; Lizhi Chen; Tianxin Lin; Yining Hua; et al. (Science of The Total Environment, 2024)

Fabrication of graphene oxide/ammonium molybdophosphate composite membrane for decontamination of cesium ions from seawater - Xiao-Yi Tang; Zi-Jie Li; Lin Wang; Peng-Cheng Zhang; Kong-Qiu Hu; Li-Rong Zheng; Zhi-Hui Zhang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Bamboo vinegar regulates the phytoremediation efficiency of Perilla frutescens (L.) Britt. by reducing membrane lipid damage and increasing cadmium retention - Zhenguo Li; Xingyu Hao; Tianlian He; Ying Chen; Mingwei Yang; Cheng Rong; Chengzhen Gu; Qingtie Xiao; Ruiyu Lin; Xinyu Zheng (Journal of Hazardous Materials, 2024)

Exendin-4, a glucagon-like peptide-1 receptor agonist, alleviates muscular dysfunction and wasting in a streptozotocin-induced diabetic mouse model compared to metformin - Ding-Cheng Chan; Yuan-Cheng Lin; Huei-Ping Tzeng; Rong-Sen Yang; Meng-Tsan Chiang; Shing-Hwa Liu (Tissue and Cell, 2024)

Genomic profiling of biosynthetic potentials of medicinal secondary metabolites for ‘Aliisedimentitalea scapharcae’ KCTC 42119T, isolated from ark shell - Jin-Cheng Rong; Lin-Lin Cui; Na Li; Mao-Li Yi; Bo-Tao Huang; Qi Zhao (Marine Genomics, 2024)

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

Chemical constituents of the deep-sea-derived fungus Trichoderma simmonsii ZEN3 and their chemotaxonomic significance - Li-Fang Liu; Yuan Wang; Rong Chao; Lin Xu; Zheng-Biao Zou; Kai Zhang; Ming-Min Xie; Xian-Qiang Chen; Cheng-Hai Gao; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Repair of tendons treated with peracetic acid–ethanol and gamma irradiation by EDC combined with NHS: a morphological, biochemical and biomechanical study in vitro - Rong-xing Ma; Rui-feng Li; Xiao-qiang Deng; Rui-qi Qiao; Ji-kai Li; Kun-xiu Song; Shao-lin Ji; Yong-cheng Hu (Cell and Tissue Banking, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

hOGG1: A novel mediator in nitrosamine-induced esophageal tumorigenesis - De-Rong Tang; Cheng-Lin Li; Zhi-Yun Xu; Zhen-Zhong Zhang; Qian-Wei Wang; Jian-Qiang Zhao (Food and Chemical Toxicology, 2024)

In vitro and in vivo protective potential of quercetin-3-glucuronide against lipopolysaccharide-induced pulmonary injury through dual activation of nuclear factor-erythroid 2 related factor 2 and autophagy - Pei-Rong Yu; Chiao-Yun Tseng; Cheng-Chin Hsu; Jing-Hsien Chen; Hui-Hsuan Lin (Archives of Toxicology, 2024)

First insights into the bioaccumulation, biotransformation and trophic transfer of typical tetrabromobisphenol A (TBBPA) analogues along a simulated aquatic food chain - Chuan-Sheng Sun; Sheng-Wu Yuan; Rui Hou; Si-Qi Zhang; Qian-Yi Huang; Lang Lin; Heng-Xiang Li; Shan Liu; Yuan-Yue Cheng; Zhi-Hua Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

New insight into the bioaccumulation and trophic transfer of free and conjugated antibiotics in an estuarine food web based on multimedia fate and model simulation - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Pelagibacterium flavum sp. nov., Isolated from Soil Sample - Xue-Mei Chen; Zu-Zhen Yang; Si-Rong He; Lian-Shuang Xiong; Qing Yuan; Shu-Ya Zuo; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2024)

Steroid metabolites as overlooked emerging contaminants: Insights from multimedia partitioning and source–sink simulation in an estuarine environment - Ru Xu; Shan Liu; Yun-Feng Pan; Nian-Nian Wu; Qian-Yi Huang; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Yuan-Yue Cheng (Journal of Hazardous Materials, 2024)

Mystery of bisphenol F-induced nonalcoholic fatty liver disease-like changes: Roles of Drp1-mediated abnormal mitochondrial fission in lipid droplet deposition - Linwei Zhang; Xuexue Xie; Jingxian Tao; Sizhe Wang; Miaoyang Hu; Xi Wang; Zheng Yu; Liuting Xu; Yuxin Lin; Weilan Wu; Jie Cheng; Linlin Wu; et al. (Science of The Total Environment, 2023)

Complete genome analysis of type strain of a novel bacterial family Temperatibacteraceae fam. nov., isolated from surface seawater - Jin-Cheng Rong; Lin-Lin Cui; Xiao-Chen Yang; Mao-Li Yi; Qi Zhao (Marine Genomics, 2023)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

Litter traps: A comparison of four marine habitats as sinks for anthropogenic marine macro-litter in Singapore - Jenny Fong; Samuel Hsien Rong Lee; Yuchen Sun; Cheng Ling Lim; Yean Ai Jolin Tan; Yi Hong Tan; Mei Lin Neo (Marine Pollution Bulletin, 2023)

Vertical distribution and transport of microplastics in the urban atmosphere: New insights from field observations - Zhen Yuan; Cheng-Lei Pei; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Kai Zhang; Ming-Gang Cai; Xiang-Rong Xu (Science of The Total Environment, 2023)

Superior performance of a membrane bioreactor through innovative in-situ aeration and structural optimization using computational fluid dynamics - Liguo Shen; Qihang Wu; Qunfeng Ye; Hongjun Lin; Jianzhen Zhang; Cheng Chen; Rong Yue; Jiaheng Teng; Huachang Hong; Bao-Qiang Liao (Water Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Black phosphorus quantum dots induced ferroptosis in lung cell via increasing lipid peroxidation and iron accumulation - Liangding Dou; Rong Liu; Zhaojizhe Wang; Zhi Huang; Lei Wang; Mo Lin; Xin Hou; Jinwen Zhang; Tantan Cheng; Qi He; Dai Wang; Dongbei Guo; et al. (Food and Chemical Toxicology, 2023)

Applicability of carbonate clumped isotope thermometry in the Tuchang-Jentse geothermal field - Yi-Chia Lu; Sheng-Rong Song; Ling-Wen Liu; Tsung-Ren Peng; Bill Bing-Cheng Chen; Remy Kai-Cheng Tu; Li-Hung Lin; Pei-Ling Wang (Geothermics, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Rice OsHsp16.9A interacts with OsHsp101 to confer thermotolerance - Yi-Hsin Liu; Tong-Seung Tseng; Ching-Rong Wu; Shu-Ting Cho; Chih-Horng Kuo; Xin-Jie Huang; Jung-Yi Cheng; Kuo-Hsuan Hsu; Kung-Fu Lin; Chia-Chin Liu; Ching-Hui Yeh (Plant Science, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Whole-genome sequencing reveals putative underlying mechanisms of biocontrol capability of IBFCBF-5 - Chen Luo; Ai-rong Shen; Ye-song Ren; Yang Zhai; Yi Cheng; Jianping Xu; Lin Wei; Ji-lie Li; Liang-bin Zeng (Acta Physiologiae Plantarum, 2023)

Advances in post-operative prognostic models for hepatocellular carcinoma - Ziqin He; Xiaomin She; Ziyu Liu; Xing Gao; Lu Lu; Julu Huang; Cheng Lu; Yan Lin; Rong Liang; Jiazhou Ye (Journal of Zhejiang University-SCIENCE B, 2023)

Effects of demineralization mode and particle size of allogeneic bone powder on its physical and chemical properties - Kun-xiu Song; Shao-lin Ji; Yong-jie Zhao; Hao-ran Zhang; Rong-xing Ma; Jing-yu Zhang; Yong-cheng Hu (Cell and Tissue Banking, 2023)

The effect of isovitexin on lipopolysaccharide-induced renal injury and inflammation by induction of protective autophagy - Chiao-Yun Tseng; Pei-Rong Yu; Cheng-Chin Hsu; Hui-Hsuan Lin; Jing-Hsien Chen (Food and Chemical Toxicology, 2023)

Expanded polystyrene buoys as an important source of hexabromocyclododecanes for aquatic ecosystem: Evidence from field exposure with different substrates - Yun-Feng Pan; Shan Liu; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Environmental Pollution, 2023)

Short-Term Limited Water Irrigation Influences the Photosynthetic Pigments, Enzymatic and Non-Enzymatic Activities in Saccharum spontaneum L. at Vegetative Stage - Zhi-Nian Deng; Hai-Rong Huang; Cheng-Mei Huang; Krishan K. Verma; Hai-Bin Luo; Sheng-Li Jiang; Yi-Jie Li; Hui-Qing Cao; Kai-Chao Wu; Lin Xu (Sugar Tech, 2023)

Impacts of 2 and 4°C global warmings on extreme temperatures in Taiwan - I‐Chun Tsai; Pei‐Rong Hsieh; Chao‐Tzuen Cheng; Yu‐Shiang Tung; Lee‐Yaw Lin; Huang‐Hsiung Hsu (International Journal of Climatology, 2023)
Extreme temperatures were considered natural hazards because they could increase morbidity and mortality. Understanding the extreme temperature changes at different warming levels is crucial to climate change mitigation and adoption for human health. This study projected climate change effects on the intensity, occurrence, and duration of extreme temperatures in Taiwan with 2 and 4°C global warming scenarios using the Weather Research and Forecasting model. The future climate simulations were conducted with the pseudo‐global warming approach, and the future climate changes were obtained from the ensemble mean of simulations in the Coupled Model Intercomparison Project 5. The simulated daily mean temperature increased by 1.40 and 3.09°C under 2 and 4°C global warmings. In a warming world, the daily maximum temperature was projected to increase by 1.35–3.00°C, whereas the daily minimum temperature was even higher, leading to weaker diurnal temperature variation in most regions. The simulation results show that intensified heatwaves with frequent and prolonged durations become par for the course, whereas extremely cold days disappear gradually. The occurrence of heatwaves in the future is projected to be five times that in the current climate. Comparing the global warming impacts over different land‐use types, the heatwave occurrence over urban areas rose more quickly than over other land‐use types; forests are less vulnerable to global warming. On the contrary, the changes in extremely cold days over urban areas were weaker than over other land‐use types. Overall, the effects of global warming on temperature revealed that extreme events were more severe with increased temperature than with the mean state of air temperature. Nonlinear behaviours indicated that global warming should be limited to 2°C, and the additional 2°C warming (from 2 to 4°C) should be addressed carefully.

Revealing microcystin-LR ecotoxicity to earthworm (Eisenia fetida) at the intestinal cell level - Xiang Liu; Jin-Cheng Ye; Fen Li; Rong-Jun Gao; Xiao-Xiao Wang; Ji-Liang Cheng; Bai-Lin Liu; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; et al. (Chemosphere, 2023)

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)

Effects of Diversified Cropping Sequences and Tillage Practices on Soil Organic Carbon, Nitrogen, and Associated Fractions in the North China Plain - Ahmad Latif Virk; Wen-Sheng Liu; Jia-Rui Niu; Cheng-Tang Xu; Qiu-Yue Liu; Zheng-Rong Kan; Xin Zhao; Hai-Lin Zhang (Journal of Soil Science and Plant Nutrition, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Roles of moisture sources and transport in precipitation variabilities during boreal summer over East China - Qu-cheng Chu; Rong Zhi; Qi-guang Wang; Guo-lin Feng (Climate Dynamics, 2019)

Two new benzophenones from endohydric moss Polytrichum Commune - Xu-Hong Duan; Jian-Cheng Zhao; Lin Li; Lin Pei; Pei He; Rong Wang (Natural Product Research, 2019)

Immune Cells After Ischemic Stroke Onset: Roles, Migration, and Target Intervention - Lu-yao Ao; Yun-Yi Yan; Lin Zhou; Cheng-yuan Li; Wan-Ting Li; Wei-rong Fang; Yun-man Li (Journal of Molecular Neuroscience, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Cyclooxygenase-2 (COX-2) polymorphism rs689466 may contribute to the increased susceptibility to post-traumatic osteomyelitis in Chinese population - Lei Wang; Nan Jiang; Qing-rong Lin; Cheng-he Qin; Yan-jun Hu; Bin Yu (Infectious Diseases, 2017)

Lipid accumulation and anti-rotifer robustness of microalgal strains isolated from Eastern China - Cheng Yuan; Yan-Lin Zheng; Wan-Lu Zhang; Ru He; Yong Fan; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2017)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

ApoA-I induces S1P release from endothelial cells through ABCA1 and SR-BI in a positive feedback manner - Xing Liu; Kun Ren; Rong Suo; Sheng-Lin Xiong; Qing-Hai Zhang; Zhong-Cheng Mo; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

G2 rotavirus within an emergent VP7 evolutionary lineage circulating in children with acute diarrhea in Guangxi Province of China, 2014 - Hui Jin Dong; Yuan Qian; You Zhang; Lin Qing Zhao; Ru Nan Zhu; Yi Nong; Zhao Jun Mo; Rong Cheng Li (Archives of Virology, 2016)

Increasing the immune activity of exosomes: the effect of miRNA-depleted exosome proteins on activating dendritic cell/cytokine-induced killer cells against pancreatic cancer - Ri-sheng Que; Cheng Lin; Guo-ping Ding; Zheng-rong Wu; Li-ping Cao (Journal of Zhejiang University-SCIENCE B, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

Schwann cells induce Proliferation and Migration of Oligodendrocyte Precursor Cells Through Secretion of PDGF-AA and FGF-2 - Yue-Juan Chen; Jing-Xing Zhang; Lin Shen; Qi Qi; Xiao-Xin Cheng; Zheng-Rong Zhong; Zhi-Quan Jiang; Rui Wang; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2015)

Prauserella endophytica sp. nov., an endophytic actinobacterium isolated from Tamarix taklamakanensis - Jia-Meng Liu; Xugela Habden; Lin Guo; Li Tuo; Zhong-Ke Jiang; Shao-Wei Liu; Xian-Fu Liu; Li Chen; Rong-Feng Li; Yu-Qin Zhang; Cheng-Hang Sun (Antonie van Leeuwenhoek, 2015)

Rapid detection of copper chlorophyll in vegetable oils based on surface-enhanced Raman spectroscopy - Wei-Nan Lian; Jessie Shiue; Huai-Hsien Wang; Wei-Chen Hong; Po-Han Shih; Chao-Kai Hsu; Ching-Yi Huang; Cheng-Rong Hsing; Ching-Ming Wei; Juen-Kai Wang; Yuh-Lin Wang (Food Additives & Contaminants: Part A, 2015)

First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

Changes in the potential habitats of 10 dominant evergreen broad-leaved tree species in the Taiwan-Japan archipelago - Katsuhiro Nakao; Motoki Higa; Ikutaro Tsuyama; Cheng-Tao Lin; Shih-To Sun; Jian-Rong Lin; Chyi-Rong Chiou; Tzu-Ying Chen; Tetsuya Matsui; Nobuyuki Tanaka (Plant Ecology, 2014)

Use of motor abundance in old adults in the regulation of a narrow-based stance - Wei-Li Hsu; Kwan-Hwa Lin; Rong-Sen Yang; Chih-Hsiu Cheng (European Journal of Applied Physiology, 2014)

A fully automatic registration approach based on contour and SIFT for HJ-1 images - XiLiang Ni; ChunXiang Cao; Lin Ding; Tao Jiang; Hao Zhang; HuiCong Jia; GuangHe Li; Jian Zhao; Wei Chen; Wei Ji; Min Xu; MengXu Gao; et al. (Science China Earth Sciences, 2012)

Spermidine affects the transcriptome responses to high temperature stress in ripening tomato fruit - Lin Cheng; Rong-rong Sun; Fei-yan Wang; Zhen Peng; Fu-ling Kong; Jian Wu; Jia-shu Cao; Gang Lu (Journal of Zhejiang University-SCIENCE B, 2012)

Blockade of acid-sensing ion channels protects articular chondrocytes from acid-induced apoptotic injury - Wei Hu; Fei-Hu Chen; Feng-Lai Yuan; Teng-Yue Zhang; Fan-Rong Wu; Chao Rong; Sheng Jiang; Jie Tang; Cheng-Cheng Zhang; Mei-Ying Lin (Inflammation Research, 2012)

Acute effects of plyometric jumping and intermittent running on serum bone markers in young males - Che-Fu Lin; Tsang-hai Huang; Kuo-Cheng Tu; Linda L. Lin; Yi-Hsuan Tu; Rong-Sen Yang (European Journal of Applied Physiology, 2012)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

Establishment of a transgene expression system for the marine microalga Schizochytrium by 18S rDNA-targeted homologous recombination - Ru-Bin Cheng; Xiang-Zhi Lin; Zhao-Kai Wang; Shan-Jun Yang; Hui Rong; Yong Ma (World Journal of Microbiology and Biotechnology, 2011)

PTEN status is related to cell proliferation and self-renewal independent of CD133 phenotype in the glioma-initiating cells - Ru-Bin Cheng; Rui-Juan Ma; Zhao-Kai Wang; Shan-Jun Yang; Xiang-Zhi Lin; Hui Rong; Yong Ma (Molecular and Cellular Biochemistry, 2011)

Methylobacterium soli sp. nov. a methanol-utilizing bacterium isolated from the forest soil - Yan-Ru Cao; Qian Wang; Rong-Xian Jin; Shu-Kun Tang; Yi Jiang; Wen-Xiang He; Hang-Xian Lai; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2011)

Construction of a recombinant adenovirus vector expressing IL-18BP/IL-4 fusion gene and the anti-inflammatory effect induced by this gene on lipopolysaccharide-stimulated synovial fibroblasts - Hang-Ping Yao; Yun Qian; Xue-Ting Shao; Zhe-Rong Xu; Lin-Fang Cheng; Lei Feng; Nan-Ping Wu; Yun-Mei Yang (Inflammation Research, 2010)

Medium optimization for the feather-degradation by Streptomyces fradiae Var S-221 using the response surface methodology - Xin Cheng; Lin Huang; Xiao-rong Tu; Kun-tai Li (Biodegradation, 2010)

Rejecting strictly allopatric speciation on a continental island: prolonged postdivergence gene flow between Taiwan ( Leucodioptron taewanus , Passeriformes Timaliidae) and Chinese ( L. canorum canorum ) hwameis - JING-WEN LI; CAROL K. L. YEUNG; PI-WEN TSAI; RONG-CHIEN LIN; CHIA-FEN YEH; CHENG-TE YAO; LIANXIAN HAN; LE MANH HUNG; PING DING; QISHAN WANG; SHOU-HSIEN LI (Molecular Ecology, 2010)

Phylogenetic analysis of Mycoplasma suis isolates based on 16S rRNA gene sequence in China - Rong-Qiong Zhou; Kui Nie; Han-Cheng Huang; Shi-jun Hu; Zuo-yong Zhou; Hong-Lin Luo (Veterinary Research Communications, 2009)

Chemical constituents from the leaves of Machilus zuihoensis Hayata var. mushaensis (Lu) Y.C. Liu - Chung-Yi Chen; Ming-Jen Cheng; Yi-Jung Chiang; Jia-Chi Bai; Chih-Tsao Chiu; Rong-Jyh Lin; Yen-Ray Hsui; Wen-Li Lo (Natural Product Research, 2009)

Cistanche deserticola Ma cultivated as a new crop in China - Rong Xu; Jun Chen; Shi-Lin Chen; Tong-Ning Liu; Wei-Cheng Zhu; Jiang Xu (Genetic Resources and Crop Evolution, 2009)

An analytical algorithm with a wave age factor for altimeter wind speed retrieval - Yongcun Cheng; Qing Xu; Yuguang Liu; Hui Lin; Peng Xiu; Xiaobin Yin; Haibo Zong; Zengrui Rong (International Journal of Remote Sensing, 2008)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Four new aromatic allenic ethers from the fungus Xylaria sp. No. 2508 - San-Yong Wang; Zhong-Liang Xu; Wei-Wei Mao; Zhi-Gang She; Ni Tan; Chun-Rong Li; Yong-Cheng Lin (Natural Product Research, 2008)

OsGLU1, A Putative Membrane-bound Endo-1,4-ß-D-glucanase from Rice, Affects Plant Internode Elongation - Hua-Lin Zhou; Si-Jie He; Yang-Rong Cao; Tao Chen; Bao-Xing Du; Cheng-Cai Chu; Jin-Song Zhang; Shou-Yi Chen (Plant Molecular Biology, 2006)

DNA extraction from archival formalin-fixed, paraffin-embedded tissues: heat-induced retrieval in alkaline solution - Shan-Rong Shi; Ram Datar; Cheng Liu; Lin Wu; Zina Zhang; Richard J. Cote; Clive R. Taylor (Histochemistry and Cell Biology, 2004)

A rapid and efficient DNA minipreparation suitable for screening transgenic plants - Rong-Cheng Lin; Zai-Song Ding; Liang-Bi Li; Ting-Yun Kuang (Plant Molecular Biology Reporter, 2001)